Role of hexamethylenetetramine in ZnO-cellulose nanocomposite enabled UV and humidity sensor. (January 2020) - Sahoo, Karunakar; Mohanty, Biswajyoti; Biswas, Amrita; Nayak, Jhasaketan
Abstract: Spherical nanoparticles and short nanorods of ZnO nanocrystals were grown on cellulose fibers by a simple one pot aqueous chemical bath deposition technique using hexamethylenetetramine (HMT) as the surfactant. The role of surfactant on UV and humidity sensing properties of ZnO-cellulose nanocomposite (ZCN) has been investigated. The structure, morphology and composition of the ZCNs were investigated by X-rays diffraction, field emission scanning electron microscopy and thermogravimetric analysis, respectively. The morphology, shape and size of the ZCN were analyzed by a transmission electron microscopy. The optical properties were investigated by diffuse reflectance spectroscopy (DRS). The band gap values of the composites, obtained from DRS, were in the range of 3.22–3.24 eV. The ZCN synthesized with 0.9 wt% of HMT showed a very high response to ultraviolet (UV) light, characterized by a large increase in the photocurrent under UV illumination. Due to UV illumination, the surface photocurrent recorded from a pellet of the above nanocomposite powder increased from 7.416 × 10 −7 A to 3.161 × 10 −5 A in 8 s. The ON to OFF ratio of the photocurrent ( I UV / I Dark ) was 42.624, whereas the response and recovery times were 8 s and 10 s, respectively. The humidity sensing properties of the nanocomposite powder were studied in the relative humidity (RH) range 40–90% and a sensitivity of 4.487 MΩ/%RH was recorded for the powder synthesized at optimized condition. The high ON/OFF ratio, short response and recovery time imply the importance of the material as a good UV sensor, whilst the notable sensitivity of the material promises for efficient humidity sensing applications.